Mnich i teolog – charakterystyka Świętych Braci na podstawie tekstów liturgicznych - Ławreszuk, Marek (Elpis, 2014)
The role of the liturgical text is far more complex than we think. It’s not only an inspiration for our petitions or thanksgiving, but also source of knowledge and spiritual education. Subject of this paper is to show characteristic of St Cyril and Methodius on the basis of the liturgical texts. In the minds of the faithful, their mission and activities are consistent and comprehensive, but liturgical texts devoted to the Holy Brothers show two ways how they followed in order to achieve their main goal – to spread Christianity and lead catechetical mission. St Cyril and Methodius had realized their mission on different paths, focusing on different priorities. The activity of St Methodius can be defined as the ascetic way, a sensitization to the spiritual richness of Orthodoxy. Referring to the liturgical texts the mission of St Cyril can be characterized as an educational, polemical and apologetic activity. Compliance of the liturgical texts with the life of St Cyril and Methodius and preservation of the historical resources, allows us to treat them as a valuable source of knowledge. This confirms the assertions about the nature the liturgical texts, which are an inherent aspect of the Holy Tradition of the Orthodox Church.